2016
DOI: 10.1007/s40262-016-0390-7
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Weight and CYP3A5 Genotype on the Population Pharmacokinetics of Tacrolimus in Stable Paediatric Renal Transplant Recipients

Abstract: In patients beyond the first year after transplantation, there is a cumulative effect of CYP3A5*1 polymorphism and weight on the tacrolimus C 0. Children with lower weight and carriers of the CYP3A5*1 allele have higher weight-normalised tacrolimus dose requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
36
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 67 publications
9
36
0
Order By: Relevance
“…Tacrolimus is strongly bound to red blood cells . Several studies showed that plasma tacrolimus concentrations change with altering hematocrit levels . However, Storset et al suggested that this influence might not always be clinically relevant because hematocrit is not expected to influence the unbound, therapeutically active fraction of tacrolimus .…”
Section: Discussionmentioning
confidence: 99%
“…Tacrolimus is strongly bound to red blood cells . Several studies showed that plasma tacrolimus concentrations change with altering hematocrit levels . However, Storset et al suggested that this influence might not always be clinically relevant because hematocrit is not expected to influence the unbound, therapeutically active fraction of tacrolimus .…”
Section: Discussionmentioning
confidence: 99%
“… AUC area under the concentration time curve, wb whole blood a Targets according to our local hospital protocol which is based on the following references: [3, 8]…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the intra- and inter-individual pharmacokinetic variability is high [1, 5]. Previously, body weight [68], CYP3A5 polymorphisms [69], age [9, 10] and hematocrit level [6, 7] were found to have significant effects on pharmacokinetic variability in pediatric kidney transplant patients, especially in the early phase after transplantation. Due to the large pharmacokinetic variability, individualizing tacrolimus dosing regimens by performing therapeutic drug monitoring (TDM) to optimize the therapeutic effect and minimize adverse effects is essential and currently the standard of care.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies demonstrated a non‐linear relationship between drug clearance and body weight in paediatric patients . As is well known, tacrolimus is metabolized by CYP3A5 , and its clearance rate is different in different genotypes . Wuzhi capsule is a Chinese patent medicine whose primary active constituents are schisandrin, schisantherin A, and schisandrol B, and it can increase tacrolimus concentration via inhibiting tacrolimus metabolism enzyme, CYP3A .…”
Section: Discussionmentioning
confidence: 99%